Effects of biocementation on some properties of cement-based materials incorporating Bacillus Species bacteria – a review - Mutitu, Karanja D.; Munyao, Mulwa O.; Wachira, Jackson M.; Mwirichia, Romano K.; Thiong'o, Karanja J. (Taylor and Francis, 2019)
There is a growing need in the construction industry to improve transfer and durability aspects of Portland pozzolana cement. Ureolytic bacteria have recently emerged as potential micro-organisms well known for precipitation of calcium carbonate through microbiologically induced calcite precipitation (MICP) process. MICP process has emerged as a viable mechanism for improvement of the PPC performance. This paper presents an in-depth discussion on the effects of Bacillus pseudofirmus, Bacillus sphaericus, Sporosarcina pasteurii, Bacillus cereus, Bacillus megaterium and Bacillus subtilis on some selected physico-mechanical properties of cement-based materials. These properties include standard consistency, setting time, compressive strength, water absorptivity, porosity and chloride ingress. The influence of pH, temperature and various bacteria nutrient requirements on optimum MICP process is also presented. In conclusion, benefits and drawbacks on the use of MICP has been discussed. MICP as a potential technique for improvement of physico-mechanical properties as well as repair of cracked cement-based structures has been discussed.
Keywords: alkaliphilic; bacteria; biocementation; calcite precipitation; cement; microbially mediated reactions